(untitled) (Journal of Organizational Psychology, 2023)
This research provides valuable insights into the impact of COVID-19 on the education system, the need for adaptation, and the importance of various aspects such as experiential learning, emotional well being, mental health, workplace and online education. It offers recommendations and considerations for policymakers and practitioners in higher education to navigate the post-pandemic world successfully.